Diagnostic comparison between FECPAKG2 and the Kato-Katz method for analyzing soil-transmitted helminth eggs in stool. - Wendelin Moser; Oliver Bärenbold; Greg J Mirams; Piet Cools; Johnny Vlaminck; Said M Ali; Shaali M Ame; Jan Hattendorf; Penelope Vounatsou; Bruno Levecke; Jennifer Keiser (Public Library of Science (PLoS), 2018)
Over one billion people are infected with soil-transmitted helminths (STH), i.e. Ascaris lumbricoides, hookworm and Trichuris trichiura. For estimating drug efficacy and monitoring anthelminthic drug resistance, accurate diagnostic methods are critical. FECPAKG2 is a new remote-diagnostic tool used in veterinary medicine, which produces an image of the stool sample that can be stored on an internet cloud. We compared for the first time FECPAKG2 with the recommended Kato-Katz method.Two stool samples were collected from adolescent participants (age 15-18 years) at baseline and 14 to 21 days after treatment in the framework of a randomized clinical trial on Pemba Island, Tanzania. Stool samples were analyzed with different diagnostic efforts: i) one or ii) two Kato-Katz thick smears from the first sample, iii) two Kato-Katz thick smears from two samples and iv) FECPAKG2 from the first sample. Parameters were calculated based on a hierarchical Bayesian egg count model. Complete data for all diagnostic efforts were available from 615 participants at baseline and 231 hookworm-positive participants at follow-up. At baseline FECPAKG2 revealed a sensitivity of 75.6% (72.0-77.7) for detecting A. lumbricoides, 71.5% (67.4-95.3) for hookworm and 65.8% (64.9-66.2) for T. trichiura, which was significantly lower (all p<0.05) than any of the Kato-Katz methods and highly dependent on infection intensity. Despite that the egg counts based on FECPAKG2 were relatively lower compared to Kato-Katz by a ratio of 0.38 (0.32-0.43) for A. lumbricoides, 0.36 (0.33-0.40) for hookworm and 0.08 (0.07-0.09) for T. trichiura, the egg reduction rates (ERR) were correctly estimated with FECPAKG2.The sensitivity to identify any STH infection was considerably lower for FECPAKG2 compared to Kato-Katz. Following rigorous development, FECPAKG2 might be an interesting tool with unique features for epidemiological and clinical studies.